Validation of the Chinese version of the kidney transplant understanding tool in Chinese patients - Hangxia Ma; Maosen Hu; Jingjing Wan (Wiley, 2023)
Abstract Aims To evaluate the reliability and validity of the Chinese version of the Kidney Transplant Understanding Tool (K‐TUT) among patients in China. Design Cross‐sectional study. Methods A convenience sample of 171 kidney transplant (KT) candidates and 272 KT recipients was recruited from two tertiary and Grade A hospitals in Hunan Province, China. The reliability was calculated by half‐fold reliability, test-retest reliability and Cronbach's alpha. The validity was analysed by the content validity index. Results For KT candidates, the Chinese version of K‐TUT deleted items 4, 6, 7 and 8, Cronbach's α coefficient was 0.778, half‐fold reliability values were 0.792, and test-retest reliability values were 0.902. For KT recipients, the tool deleted items 3, 4, 6, 7 and 8, Cronbach's α coefficient was 0.769, half‐fold coefficient values were 0.701, and retest coefficient values were 0.888. The content validity index was 0.967. Conclusions The K‐TUT is an acceptable and reliable measurement for evaluating the relevant knowledge of KT recipients and candidates. Impact It is anticipated that this new tool will help the nursing staff to identify specific areas of deficiency that could be targeted in health education to improve the KT knowledge of patients.